Formování lidských zdrojů firmy v podmínkách transformace - Makarov, Věroslav (Univerzita Pardubice, 2001)
This paper deals with changes in conception of HRM of a company in contemporary market environment. The first part characterizes generally, traditional conception of personnel management in a company, and briefly describe its main parts. The course, which human resource management should in contemporaneity and namely in future go, is introduced in the second part. Theoretical reflections are compared with a practical approach in Czech Saving Bank (Česká spořitelna).
Keywords: transformace ekonomiky; firemní politika; Lidské zdroje; personální řízení; Česká spořitelna, a.s.